Assessment of total dissolved gas supersaturation stress on passage performance of bighead carp (Hypophthalmichthys nobilis) in vertical slot fishway - Li, Minne; Ou, Yadong; Liao, Jialin; Shi, Haoran; Zhu, Bo; Li, Xintong; Yuan, Quan; Yang, Xin (Frontiers in Marine Science, 2025)
Total dissolved gas supersaturation (TDGS) due to flood or hydropower station discharge adversely affects the swimming performance of migratory fish, thereby reducing passage efficiency. This study assessed the swimming performance of bighead carp in an experimental vertical slot fishway under varied slot flow velocities of 0.2, 0.25, and 0.3 m/s after 2 h of exposure to different levels of TDGS water. The results demonstrated that increased TDGS levels and flow velocities significantly reduced the fish passage efficiency. Specifically, passage success rates reached 61%, 48%, 37%, and 37% at TDGS levels of 100%, 110%, 120%, and 130% respectively, at a flow velocity of 0.2 m/s. At flow velocities of 0.2, 0.25, and 0.3 m/s with 100% TDGS water, success rates were 61%, 53%, and 47%, respectively. Moreover, increased TDGS levels and increased flow velocities notably extended the passage time in the fishway. Both TDGS levels and fishway flow velocities significantly influenced the swimming trajectories of the fish. Preferences for flow velocities were notably affected by the TDGS levels, whereas preferences for turbulent kinetic energy were affected by both the TDGS levels and the velocities of the fishway flow. In this study, an evaluation method was developed to assess the adverse effects of TDGS on fish passage efficiency based on the following critical parameters: passage success rate, time, trajectory, and preferred hydraulic factor. This study offers valuable insights for optimizing operations and fishway management to enhance fish protection.